Effect of negative emotions in consumption during the COVID-19 pandemic: A study from Peru - Regalado-Pezúa, Otto (2023)
The research examines the negative consumer emotions generated by the perception of social networks or traditional media with consumer behavior during the covid_19 pandemic. The study was developed in Peru with a sample of 220 consumers; the design is quantitative and structural equations were used for data processing. The results indicate that social networks and traditional media are not related to negative emotions, but are related to the change in consumer behavior in the purchase of more products and new products. The research has theoretical implications since it provides evidence to the literature that the negative emotions generated during the covid_19 pandemic are related to changes in consumer behavior, which affect the purchase of more products and new products. The practical implications of the research is for businessmen on the causes of changes in consumer behavior generated during crises. like the COVID-19 pandemic.